2016
DOI: 10.4330/wjc.v8.i3.247
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein abnormalities in South Asians and its association with cardiovascular disease: Current state and future directions

Abstract: South Asians have a high prevalence of coronary heart disease (CHD) and suffer from early-onset CHD compared to other ethnic groups. Conventional risk factors may not fully explain this increased CHD risk in this population. Indeed, South Asians have a unique lipid profile which may predispose them to premature CHD. Dyslipidemia in this patient population seems to be an important contributor to the high incidence of coronary atherosclerosis. The dyslipidemia in South Asians is characterized by elevated levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 78 publications
2
77
0
Order By: Relevance
“…South Asians make up 1/5 th of the world population and Asian Indians are a majority in this group (6). India has an estimated 31.8 million people with CAD, and the incidence of CAD in this population is expected to grow.…”
Section: Introductionmentioning
confidence: 99%
“…South Asians make up 1/5 th of the world population and Asian Indians are a majority in this group (6). India has an estimated 31.8 million people with CAD, and the incidence of CAD in this population is expected to grow.…”
Section: Introductionmentioning
confidence: 99%
“…The association demonstrated in the present review is significantly stronger among Asians ( P ‐value <.0001) compared with Latin Americans ( P ‐value = .01). South Asians, which refer to people who have ancestral origins in the Indian subcontinent (eg, India, Pakistan, Bangladesh, Sri Lanka, and Nepal), are genetically predisposed to hypercholesterolemia, thus presenting marked difficulty in reducing serum cholesterol levels . Thus, it is suggested that for an acute decrease in the levels of this lipid, as those associated with severe dengue conditions, it is necessary that the responsible event of this phenomenon presents itself a sufficient intensity to overcome this genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…South Asians, which refer to people who have ancestral origins in the Indian subcontinent (eg, India, Pakistan, Bangladesh, Sri Lanka, and Nepal), are genetically predisposed to hypercholesterolemia, thus presenting marked difficulty in reducing serum cholesterol levels. 43 Thus, it is suggested that for an acute decrease in the levels of this lipid, as those associated with severe dengue conditions, it is necessary that the responsible event of this phenomenon presents itself a sufficient intensity to overcome this genetic predisposition. Latin Americans population, in turn, present serum cholesterol levels more sensitive to environmental variations, which make this association in the population less robust.…”
Section: Discussionmentioning
confidence: 99%
“…The HDL cholesterol particles also tend to be smaller and are more often dysfunctional. Moreover, there is an increased prevalence of highly atherogenic, small dense LDL particles, even though the total LDL level is on a par with that of other population groups (8,9,16). It also appears that hyperglycaemia has a greater impact on left ventricular function in South Asians than in Caucasians, which often manifests itself as fatigue and reduced capacity for work (17,18).…”
Section: Prevalencementioning
confidence: 94%